Przegląd wybranych niekonwencjonalnych kampanii samorządowych z 2024 r. - Bajon, Mateusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This text is an analysis of selected election campaigns in the 2024 local elections in Poland, with a particular focus on their visual, symbolic and performative aspects. The author focuses on unusual, creative and innovative forms of political communication that go beyond the classic models of programmatic presentation and persuasive rhetoric. In an era of increasing fragmentation of attention, information saturation and aestheticization of public space, the effectiveness of an election campaign increasingly depends not only on substantive content, but also on the candidate`s ability to attract attention and build an emotional relationship with voters.
Keywords: kampania samorządowa; komunikacja polityczna; estetyzacja polityki; performatywność; tożsamość wizualna; strategia memiczna; marketing symboliczny; lokalna wspólnota; polityka emocji; local government campaign; political communication; aestheticization of politics; performativity; visual identity; memetic strategy; symbolic marketing; local community; politics of emotions